A sustainable future for hamlets. Albergo Diffuso and new regeneration scenarios - Giancarlo Dall’Ara; Teresa Villani (Agathón)
This paper addresses the global and unprecedented crisis that has hit the tourism industry and the great thrust towards regeneration and rebirth of hamlets, considered today as places for future living. The paper intends to provide a different reading of the accommodation model Albergo Diffuso, to highlight its potential in regeneration of hamlets, social inclusion, and repurposing of the built environment, favouring reuse and zero soil occupation. Starting from the specific features of facilities and the new ‘demand’, we present the results of a fact-finding survey aimed at developing meta-design tools, assessing impact in terms of regeneration of hamlets, and identifying strategies and actions to define best practices of operation on the built environment, with a responsible and sustainable perspective.